Supervised internship in undergraduate education in nursing: integrative review - Larissa Sapucaia Ferreira Esteves; Isabel Cristina Kowal Own Cunha; Elena Bohomol; Elaine Cristina Negri
ABSTRACT Objective: to analyze the evidence available in the literature on the contributions of the Supervised Internship in nursing training in Brazil and the teaching-learning methods employed. Method: integrative review of the literature, with search of articles published between 2002 and 2016, in PubMed, LILACS, SciELO and Eric databases. Results: Of the 4,699 articles consulted, 14 met the inclusion criteria. The analysis of these studies revealed three thematic categories: the understanding about the role of Supervised Internship; the teaching-learning processes employed; and their contributions to the training of nurses. Final considerations: this is a fundamental element in the academic training, since, depending on the didactic-pedagogical organization, it makes possible the (re) signification of the acquired knowledge throughout the course and realizes the professional competences. The teaching-learning methods are structured by the critical pedagogy, being the active methodologies the main choices of the authors.